Foreign Migration Trends of European Union Citizens in the Second Decade of the 21st Century - Iwona BĄK; Anna BARWIŃSKA-MAŁAJOWICZ; Paweł HYDZIK (Communications of International Proceedings, 2021)
Contemporary population movements constitute a serious issue, both on the social, economic and security levels, as well as in terms of creating the European Union migration policy, which is evolving towards improving instruments aimed at stimulating development. This paper presents the research results on the migration trends of European Union citizens in the second decade of the 21st century. A review of the literature and theory was conducted with a focus on workforce flows. Based on statistical data, the dynamics of emigration and immigration in individual EU countries was described. Moreover, the structure of emigrants by sex and age groups was characterised. There was a significant increase in the level of migration and significant differentiation between the studied countries.
Keywords: Migrations; European Union; Socio-Demographic Characteristics.